Evaluation of Different Security Valuation Models at Tehran Stock Exchange - Mohsen Dastgir; Mehran Hoseini Afshari (مطالعات تجربی حسابداری مالی, 2003)
After initial Pricing of stocks at Tehran stock exchange, security prices will fluctuate according to the market prices. The question is which theoretical model, the market price of securities, will follow? The aim of this study is to identify among the best theoretical models, a model, which can best define the market price. In this research, three valuation models which are best recommended in financial management literature are chosen, and the stocks which are traded at Tehran stock exchange are valued by them. Then the actual security prices, revealed by market are compared with those calculated values. The results of this study shows that if the required rate of return is calculated by CAPM, the Walter model compared to Gordon growth model and present value model of future cash flows, calculate security values closer to the market prices of the securities. The results also indicate when the fixed required rate of return of 40% is used; Gordon growth model will give values closer to the market prices of the securities.